Raising Taxes on the Wealthy to Reduce Income Inequality: International Evidence and Policy Implications for Malaysia - Wang, Linhao (Exploring Science Academic Conference Series, 2026)
Rising income inequality has renewed interest in progressive taxation as a redistribution tool. This paper reviews international evidence on the relationship between taxing the wealthy and reducing income inequality, with a focus on policy implications for Malaysia. Drawing on theoretical foundations such as the Matthew effect and optimal tax theory, the review synthesizes findings from developed and developing economies, including Belgium, Brazil, and Nordic countries. The analysis shows that well-designed progressive tax systems, combined with efficient public spending, can reduce Gini coefficients and improve social mobility without stifling economic growth. Key mechanisms include fiscal transfers, education and health investments, and conditional cash transfer programs like Bolsa Família. However, critics argue that high taxes may trigger capital flight and reduce innovation incentives. The review finds that such risks are often mitigated by strong institutions, infrastructure, and human capital. For Malaysia, which currently has a maximum tax rate of 30% and significant wealth concentration (top 1% holding 40% of wealth) [1], the evidence supports progressive tax reforms that fund public services and break intergenerational poverty cycles. Policy implications include raising top marginal rates, improving tax enforcement, and linking revenues to inclusive development programs.